Smartboard Media and Learning Motivation in Elementary Mathematics: A Case Study in Rural Indonesia - Hanna Wahyu Aruming Tyas (JF Publisher, 2026)
Conventional mathematics instruction in elementary schools has been associated with low student motivation, particularly among learners in the concrete operational stage of cognitive development. This study examined the role of interactive digital smartboard media in fostering learning motivation among fourth-grade students in mathematics at a rural elementary school in South Lampung Regency, Indonesia. A descriptive qualitative approach with a single embedded case study design was employed, involving 24 students purposively selected on the basis of preliminary evidence of low motivational engagement. Data were collected across three structured learning sessions through participatory observation, semi-structured interviews, a motivation questionnaire, and systematic field notes, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, with trustworthiness established through source and technique triangulation. Results showed a progressive increase in active engagement from 40% during conventional instruction to 85% and 92% across the two smartboard-assisted sessions, with a mean motivation score of 83.4%. Qualitative data indicated heightened curiosity, reduced reluctance, and spontaneous peer collaboration during smartboard-assisted lessons, though a small proportion of students remained less engaged. Given the purposive sampling and limited session count, these findings should be interpreted as context-specific rather than generalizable. The study nonetheless offers preliminary evidence that interactive smartboard media can stimulate learning motivation in elementary mathematics, with implications for instructional design and directions for future research using larger, unselected samples.